A study of string theory and the AdS/CFT correspondence - Bairrão, Pedro Fernandes Henriques (2025)
This dissertation consists of a comprehensive and pedagogical review of the main topics of string theory necessary for understanding Maldacena\'s original derivation of the AdS/CFT correspondence, as well as the derivation itself. The large N expansion of Yang-Mills theory is presented as the main motivation for seeking a string-theoretic language for gauge theories. The bosonic string is studied in conformal gauge, with an emphasis on the spectrum and the low energy effective actions for both closed and open strings. The properties of D-branes are studied via T-duality, and closed-open string duality is checked by explicitly computing the interaction amplitude between two D-branes. The type II superstring theories are studied in the RNS formalism and their massless spectrum is shown to match that of the type II ten-dimensional supergravity theories. Supersymmetric branes are discussed, including their realization as supergravity solitons, and the original derivation of the AdS/CFT duality is presented. Some of the properties of the correspondence are discussed, including the idea of the holographic dictionary.